2023
DOI: 10.3389/fimmu.2023.1103307
|View full text |Cite
|
Sign up to set email alerts
|

Age/autoimmunity-associated B cells in inflammatory arthritis: An emerging therapeutic target

Abstract: Age/autoimmunity-associated B cells (ABCs) are a novel B cell subpopulation with a unique transcriptional signature and cell surface phenotype. They are not sensitive to BCR but rely on TLR7 or TLR9 in the context of T cell-derived cytokines for the differentiation. It has been established that aberrant expansion of ABCs is linked to the pathogenesis of systemic autoimmune diseases such as systemic lupus erythematosus. Recently, we and other groups have shown that increased ABCs is associated with rheumatoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Memory B and plasma cells are pathogenic in autoimmune diseases; however, a new subset of cells—age/autoimmunity-associated B cells (ABCs)—has recently been suggested to contribute to autoimmunity ( 11 , 12 ). ABCs were initially identified as a cell population that increased with age; however, they expanded in mouse autoimmune models regardless of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Memory B and plasma cells are pathogenic in autoimmune diseases; however, a new subset of cells—age/autoimmunity-associated B cells (ABCs)—has recently been suggested to contribute to autoimmunity ( 11 , 12 ). ABCs were initially identified as a cell population that increased with age; however, they expanded in mouse autoimmune models regardless of age.…”
Section: Introductionmentioning
confidence: 99%
“…ABCs are often variedly defined depending on the combination of these markers. Human ABC-like B cells (including CD27 – IgD – and CD11c + CD21 lo ) are more abundant in various human autoimmune diseases, such as systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA) ( 11 , 12 ). However, molecules expressed in ABCs that are involved in autoimmune diseases are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…How the heterogeneity within ABC populations reported in different autoimmune and infectious diseases [38, 39] affects SjD is unknown. In SjD patients, the CD21 -/low B cells elevated in peripheral blood showed immunoglobulin gene rearrangement indicative of memory B cells and expressed antibodies reactive with nuclear and cytoplasmic autoantigens.…”
Section: Discussionmentioning
confidence: 99%
“…RA is an autoimmune disease. It is well known that T and B lymphocytes are essential to the etiology and progression of RA [ 104 ]. Furthermore, it has been demonstrated that joint deterioration and an aggravation of clinical symptoms are associated with autoantibodies in patients with RA [ 105 , 106 ].…”
Section: Natural Productmentioning
confidence: 99%